Differences in psychiatric symptoms among Asian patients with depression: A multi-country cross-sectional study - Ahmad H. Sulaiman (2018)
Aim The aim of this study was to compare the symptomatic and clinical features of depression among five groups of patients with major depressive disorder (MDD) living in China, Korea, Malaysia/Singapore, Taiwan, and Thailand. Methods Consecutive consenting adults (aged 18-65) who met DSM-IV criteria for non-psychotic MDD - based on the Mini International Neuropsychiatric Interview - and who were free of psychotropic medication were evaluated in a cross-sectional study. Depressive symptoms were evaluated using the 10-item Montgomery-Asberg Depression Rating Scale (MADRS) and the 13-item depression subscale of the Symptoms Checklist 90-Revised (SCL-90-R). In addition, the 10-item SCL-90-R Anxiety Subscale was completed. ancova were conducted, adjusting for confounders: age, completion of secondary education, marital status, work status, religion, index episode duration, and depressive severity. For the magnitude of differences, a threshold of 0.10 was taken as theminimum effect size representing clinical significance, and an effect size of 0.25 was considered moderate. Results Four MADRS symptoms differentiated these five groups, the most prominent being 'lassitude' and 'inner tension'. Nine SCL-90-R depression items also differentiated the groups, as did eight SCL-90-R Anxiety Subscale items. The MADRS lassitude item had the largest effect size (0.131). The rest of those statistically significant differences did not exceed 0.10. Conclusion MDD is more similar than different among outpatients in these diverse Asian countries. The between-country differences, while present and not due to chance, are small enough to enable the use of common clinician and self-report rating scales in studies involving Asians with MDD from various ethnic backgrounds. © 2013 The Authors. Psychiatry and Clinical Neurosciences © 2013 Japanese Society of Psychiatry and Neurology.